IMPLIKASI UU NO. 6 TAHUN 2014 TENTANG DESA TERHADAP PENYELENGGARAAN PEMERINTAHAN DESA - Kushandajani Kushandajani (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2016)
The existence of Law No. 6 of 2014 on Village has constructed the management of village governance, where the central government consider village as autonomous region. On the one hand, the central government accommodate the management of village government through principle of recognition, subsidiarity, diversity, unity, mutual assistance (gotong royong), kinship, deliberation, democracy, independent, participation, equality, empowerment and sustainability. Does the legal construction has implication on the social meaning of village governance? The focus of this study is to analyze changes in the meaning and reality of the implementation of the village governance, and the relation between the authority of the village and the village government structure. Qualitative method was selected, and perspective of emic was used. Data collection prioritize the use of first hand data, which were obtained from several informants through in-depth interview and focus group discussion (FGD). The results of this study show several important issues. First, four areas of village authorities, namely managing village governance, implementation of rural development, coaching rural community, and empowerment of rural community, relate to each other, where the field of development, social and community empowerment, are interpreted as a way of governing. Second, the spirit of village governance is in the local value; that is mutual assistance (gotong royong). The head of village is considered successful in running the village governance if he succeeded in building the spirit of mutual assistance of rural communities. Third, the village government managed to adapt to such change, resulting organizational structure of village government that accommodate traditional structure as well as modern organizational structure, as constructed by the State under Law No. 6 of 2014 on Village.